Seasonal dynamics of geese capillariasis - Євстаф’єва, В. О.; Єресько, В. І. (Scientific Progress & Innovations, 2018)
The article presents the results of studies of indicators of invasion of geese by the causative agent of capillariasis, depending on the season in the climatic conditions of Poltava region. The seasonal dynamics of capillariasis in geese is characterized by the increase in the extensiveness and intensity of invasion in the spring-summer period of the year (up to 54.55 % and 80.67 eggs/g) and their decrease during the winter period (12.73 %, 28.57 eggs/g). At the same time, according to the results of helminthological opening of geese, the maximum number of sexually mature capillaries was detected in winter and spring (up to 72.22 % and 37.48 specimens/head), the smallest – in summer (39.62 %, 11.86 specimens/head).